2009
DOI: 10.1099/vir.0.012864-0
|View full text |Cite
|
Sign up to set email alerts
|

NS4A regulates the ATPase activity of the NS3 helicase: a novel cofactor role of the non-structural protein NS4A from West Nile virus

Abstract: Using constructs that encode the individual West Nile virus (WNV) NS3helicase (NS3hel) and NS3hel linked to the hydrophilic, N-terminal 1-50 sequence of NS4A, we demonstrated that the presence of NS4A allows NS3hel to conserve energy in the course of oligonucleotide substrate unwinding. Using NS4A mutants, we also determined that the C-terminal acidic EELPD/E motif of NS4A, which appears to be functionally similar to the acidic EFDEMEE motif of hepatitis C virus (HCV) NS4A, is essential for regulating the ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
67
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 28 publications
1
67
0
2
Order By: Relevance
“…NS4A is regarded as a central 'organizer' of the replication complex of flaviviruses (Lindenbach & Rice, 1999;Nemésio et al, 2012;Shiryaev et al, 2009), and is composed of a hydrophilic N-terminal portion residing in the cytoplasm, three internal hydrophobic regions associated with endoplasmic reticulum (ER) membranes (pTMS1-pTMS3) and a C-terminal fragment called 2K that acts as the signal sequence for translocation of the NS4B protein into the ER lumen (Miller et al, 2007). After translocation, the 2K fragment is cleaved off the N terminus of NS4B by the host signallase in the ER lumen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS4A is regarded as a central 'organizer' of the replication complex of flaviviruses (Lindenbach & Rice, 1999;Nemésio et al, 2012;Shiryaev et al, 2009), and is composed of a hydrophilic N-terminal portion residing in the cytoplasm, three internal hydrophobic regions associated with endoplasmic reticulum (ER) membranes (pTMS1-pTMS3) and a C-terminal fragment called 2K that acts as the signal sequence for translocation of the NS4B protein into the ER lumen (Miller et al, 2007). After translocation, the 2K fragment is cleaved off the N terminus of NS4B by the host signallase in the ER lumen.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified that NS4B existed as dimers either when the protein was expressed alone in cells or in cells infected with DENV (Zou et al, 2014). Additionally, both NS4A and NS4B proteins have been demonstrated to be able to interact genetically or physically with other viral proteins, including NS3 localized in the cytoplasm (Shiryaev et al, 2009;Umareddy et al, 2006) and NS1 positioned in the ER lumen (Lindenbach & Rice, 1999;Youn et al, 2012) to modulate viral replication. For example, the hydrophilic NS4A sequence functions as a cofactor of NS3 helicase and regulates the ATPase activity of NS3 helicase (Shiryaev et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Flavivirus NS4A protein induces autophagy to prevent cell death and facilitate viral replication (24). (iv) WNV NS4A regulates the ATPase activity of NS3 helicase (25), while DENV NS4B interacts with the helicase domain of NS3 and dissociates it from singlestrand RNA (26). As noted in the accompanying article by Zou et al (27), the DENV NS3-NS4B interaction was mapped to the NS3 helicase (subdomains 2 and 3) and the NS4B cytoplasmic region (amino acids 129 to 165).…”
mentioning
confidence: 99%
“…Proteolytic removal of the 2K peptide also induces membrane alterations [40]. Recently NS4A was proven to act as a cofactor for NS3 helicase allowing the helicase to sustain the unwinding rate of the viral RNA under conditions of ATP deficiency [41]. NS4B colocalizes with viral replication complexes and proved to dissociate NS3 from single-stranded RNA, thereby enabling it to bind to a new dsRNA duplex, consequently enhancing the helicase activity and modulating viral replication [42,43].…”
Section: Introductionmentioning
confidence: 99%